Efficacy and Safety of Intravitreal Conbercept, Ranibizumab, and Triamcinolone on 23-Gauge Vitrectomy for Patients with Proliferative Diabetic Retinopathy - Jinglin Cui; Hong Chen; Hang Lu; Fangtian Dong; Dongmei Wei; Yan Jiao; Steve Charles; Weikuan Gu; Lin Wang (Journal of Ophthalmology)
Introduction. To compare the effect and safety of intravitreal conbercept (IVC), intravitreal ranibizumab (IVR), or intravitreal triamcinolone acetonide (IVTA) injection on 23-gauge (23-G) pars plana vitrectomy (PPV) for proliferative diabetic retinopathy (PDR). Methods. Fifty patients (60 eyes) of varying degrees of PDR were randomly grouped into 3 groups (1 : 1 : 1) (n=20 in each group). The 23-G PPV was performed with intravitreal conbercept or ranibizumab injection 3–7 days before surgery or intravitreal TA injection during surgery. The experiment was randomized controlled, with a noninferiority limit of five letters. Main outcome measures included BCVA, operation time, incidence of iatrogenic retinal breaks, endodiathermy rate, and silicone oil tamponade. Results. At 6 months after surgery, there were no significant differences of BCVA improvements, operation time, incidence of iatrogenic retinal breaks, endodiathermy rate, silicone oil tamponade, vitreous clear-up time, and the incidence of intraoperative bleeding between the IVC and IVR groups (all P values ≥ 0.05), but they were significantly different from the IVTA group (all P values < 0.05). IOP increases did not show significant differences between the IVC and IVR groups, but both were significantly different with the IVTA group. More patients had higher postoperative IOP in the IVTA group. Conclusions. The intravitreal injection of conbercept, ranibizumab, or TA for PDR had a significant different effect on outcomes of 23-G PPV surgery. Conbercept and ranibizumab can reduce difficulty of the operation, improve the success rate of PPV surgery, and decrease the incidence of postoperative complications.